2020
DOI: 10.2106/jbjs.19.01148
|View full text |Cite
|
Sign up to set email alerts
|

Time to Block: Early Regional Anesthesia Improves Pain Control in Geriatric Hip Fractures

Abstract: Background: Fascia iliaca nerve blocks (FIBs) anesthetize the thigh and provide opioid-sparing analgesia for geriatric patients with hip fracture awaiting a surgical procedure. FIBs are recommended for preoperative pain management; yet, block administration is often delayed for hours after admission, and delays in pain management lead to worse outcomes. Our objective was to determine whether opioid consumption and pain following a hip fracture are affected by the time to block (TTB). We also examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 32 publications
0
16
1
1
Order By: Relevance
“…First, the prospective recording of patient, nerve block, procedural, and opioid consumption data allowed accurate assessment of the timing and consumption of opioids during different phases of care. Although Garlich et al 24 report that early preoperative FI blocks reduce opioid consumption up to 2 days postoperatively, this study uniquely reports on the continued reduction of opioid consumption throughout the postoperative period and even after the FI block has worn off. To the best of our knowledge, this is also the first study to report a decrease in volume of opioids prescribed at discharge and 30-day readmission rate relating to preoperative FI block.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…First, the prospective recording of patient, nerve block, procedural, and opioid consumption data allowed accurate assessment of the timing and consumption of opioids during different phases of care. Although Garlich et al 24 report that early preoperative FI blocks reduce opioid consumption up to 2 days postoperatively, this study uniquely reports on the continued reduction of opioid consumption throughout the postoperative period and even after the FI block has worn off. To the best of our knowledge, this is also the first study to report a decrease in volume of opioids prescribed at discharge and 30-day readmission rate relating to preoperative FI block.…”
Section: Discussionmentioning
confidence: 77%
“…22 Williams et al and Garlich et al have previously demonstrated the utility of FI block in reduction of preoperative opioid use when performed in the ED. 23,24 In addition, patients receiving FI block earlier have a greater decrease in opioid consumption. 24 Thompson et al 25 investigated the use of FI block immediately before surgery for postoperative pain control and early ambulation finding a significant decrease in morphine consumption, and nonstatistically significant trend toward increased ambulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of our cases presented with viral pneumonia, fever and hypoxia; guidelines consider chest infections with systemic involvement an acceptable reason for surgical delay [28], and we considered it prudent to avoid the additional inflammatory insult of surgery on patients with systemic involvement. Long-acting regional blocks, repeated if necessary, allow patient mobilisation and facilitate care in addition to reducing opiate demand and avoiding delirium [29,30]. Daily discussion of cases among designated members of all specialties involved (internal medicine or geriatrics, orthopaedic surgeons, anaesthesiologists) is vital to determine the optimum moment of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A study in patients admitted with hip fractures indicated that a preoperative fascia iliaca nerve block resulted in lower preoperative opioid consumption, lower pain intensities, and earlier discharge. 121 Several factors discourage the use of regional anesthesia, such as lack of clinical experiences or resources and, access to an ultrasound machine which is considered standard-of-care in performing regional anesthesia. Of note, regional anesthesia technique and timing (i.e., when to perform, if a catheter can be placed, when to remove catheter) is also dependent if the patient is on anticoagulation or antiplatelet therapy or has a bleeding disorder.…”
Section: Interventional Pain Proceduresmentioning
confidence: 99%